Immunological Consequences of In Utero Exposure to Foreign Antigens - Chen, Jeng-Chang (Frontiers in Immunology, 2021)
Immunologic tolerance refers to a state of immune nonreactivity specific to particular antigens as an important issue in the field of transplantation and the management of autoimmune diseases. Tolerance conceptually originated from Owen’s observation of blood cell sharing in twin calves. Owen’s conceptual framework subsequently constituted the backbone of Medawar’s “actively acquired tolerance” as the major tenet of modern immunology. Based upon this knowledge, the delivery of genetically distinct hematopoietic stem cells into pre-immune fetuses represented a novel and unique approach to their engraftment without the requirement of myeloablation or immunosuppression. It might also make fetal recipients commit donor alloantigens to memory of their patterns as “self” so as to create a state of donor-specific tolerance. Over the years, the effort made experimentally or clinically towards in utero marrow transplantation could not reliably yield sufficient hematopoietic chimerism for curing candidate diseases as anticipated, nor did allogeneic graft tolerance universally develop as envisaged by Medawar following in utero exposure to various forms of alloantigens from exosomes, lymphocytes or marrow cells. Enduring graft tolerance was only conditional on a state of significant hematopoietic chimerism conferred by marrow inocula. Notably, fetal exposure to ovalbumin, oncoprotein and microbial antigens did not elicit immune tolerance, but instead triggered an event of sensitization to the antigens inoculated. These fetal immunogenic events might be clinically relevant to prenatal imprinting of atopy, immune surveillance against developmental tumorigenesis, and prenatal immunization against infectious diseases. Briefly, the immunological consequences of fetal exposure to foreign antigens could be tolerogenic or immunogenic, relying upon the type or nature of antigens introduced. Thus, the classical school of “actively acquired tolerance” might oversimplify the interactions between developing fetal immune system and antigens. Such interactions might rely upon fetal macrophages, which showed up earlier than lymphocytes and were competent to phagocytose foreign antigens so as to bridge towards antigen-specific adaptive immunity later on in life. Thus, innate fetal macrophages may be the potential basis for exploring how the immunological outcome of fetal exposure to foreign antigens is determined to improve the likelihood and reliability of manipulating fetal immune system towards tolerization or immunization to antigens.